The Effect of Geometry Concrete Learning Media on Students’ Mathematics Learning Outcomes - Dotu, Fadila; Yahya, Lailany; Damayanti, Taulia ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Mathematics is often perceived as a difficult subject because many of its concepts are abstract and difficult for students to visualize. The use of appropriate learning media is therefore essential to support students’ conceptual understanding, particularly in geometry topics such as plane figures. This study aims to investigate the effect of concrete object learning media on the mathematics learning outcomes of Grade VII students at SMPN 2 Suwawa. This research employed a quasi-experimental method using a Pretest–Posttest Control Group Design. The sample consisted of 36 students selected through simple random sampling and divided into an experimental group and a control group. The experimental group was taught using the Contextual Teaching and Learning (CTL) model supported by concrete object media, while the control group received CTL instruction without concrete media. Data were collected using pretests and post-tests in the form of essay questions to measure students’ cognitive understanding of plane geometry. Instrument validity and reliability were tested prior to data analysis, which included descriptive statistics and inferential tests such as normality, homogeneity, and independent t-tests. The results show that students in the experimental group achieved significantly higher post-test scores (mean = 88.27) than those in the control group (mean = 64.50). The hypothesis testing revealed a calculated t-value of 6.1028, exceeding the critical t-value of 1.691, with a very strong effect size (Cohen’s d = 2.1985). In conclusion, the use of concrete object media within the CTL model significantly improves students’ mathematics learning outcomes. This approach is effective in creating meaningful and active learning experiences, particularly for abstract mathematical topics such as plane figures.